A comparative input-output analysis of the construction sector in three developing economies of South Asia. Issue 11 (2nd November 2019) - Ali, Yousaf; Sabir, Muhammad; Muhammad, Noor
Abstract: Construction is commonly regarded as one of the major industries of an economy that is receiving a significant attention in the developing countries. This paper uses the Asian Development Bank (ADB) input-output database at constant prices for the selected Asian countries, i.e. Bangladesh, Sri Lanka and Nepal to analyze and compare the performance of the construction sector in these economies. The novelty of this research is the application of multiple linkages methods. First, the standard measures of the backward and forward linkages are used to examine the induced output created by the demand push and supply pull effects of the construction industry. Second, the concept of Hypothetical Extraction Method (HEM) is applied to extract a sector hypothetically from an economic system and then to examine the influence of that extraction on the rest of the economy. The results indicate that the construction sector has a strong backward and weak forward linkages for all the three economies. Furthermore, results reveal that the 'pull effect' is very significant in these countries while the 'push effect is very insignificant. With respect to the identification of the key sectors, the findings of the traditional methods are very different from those of the hypothetical extraction methods.